An Exploratory Study on the Efficacy of Ayurveda Interventions in Sub-Clinical Hypothyroidism: A Case Study - G.M, Maithri; Ragini, P.S Harshitha; P, Anu Krishna; Devaru, Thejesh; V. Binorkar, Sandeep; J, Divya; S S, Dhanush; Kumar B G, Chethan; M, Sneha; K. M, Anil Kumar (Journal of Neonatal Surgery, 2025)
Introduction: The modern era has seen a significant surge in endocrine disorders, of which Hypothyroidism being a prominent concern. Globally, approximately 2-5% of the population is affected, with urban India reporting a prevalence of 10.95%. The condition predominantly affects the individual in the middle age group with a higher incidence among female. If left untreated Hypothyroidism may cause chronic health complications, necessitating lifelong hormone replacement therapy. Furthermore, Sub-clinical Hypothyroidism (SCH), characterized by elevated TSH levels and normal T4 levels, can also have a profound impact on quality of life, despite being often overlooked. Consequently, there is a growing need to explore Hypothyroidism from Ayurveda perspective and develop effective management strategies rooted in this traditional system of medicine. Materials and Methods: A 33-year-old male patient visited Kayachikitsa OPD of JSSAMH on 17/06/2024 and presented with a one-year history of progressive symptoms such as hair loss, decreased appetite, weight gain, lethargy, generalized weakness, accompanied by depressive and anxious mood, and excessive rumination. Laboratory tests revealed elevated TSH levels with normal T3 and T4 six months prior. He was diagnosed with SCH and was advised to undergo Shodhana followed by Shamanoushadi for about nine months. Observations and Results: A nine-month Shamana Chikitsa and follow-up regimen yielded a notable improvement in the patient’s condition, as evidenced by a substantial decrease in TSH levels and a 70% reduction in symptom severity